Metabolomics Profiling Reveals the Role of PEDF in Triple-Negative Breast Cancer Cell MDA-MB-231 under Glycaemic Loading - Raziyeh Abooshahab; Kourosh Hooshmand; Giuseppe Luna; Hani Al-Salami; Crispin R. Dass (MDPI AG, 2023)
Pigment epithelium-derived factor (PEDF) is a secreted glycoprotein that belongs to the serine protease inhibitor (serpin) family. An increase in PEDF activity has been shown to be a potent inhibitor of tumour progression and proliferation, suggesting a possible therapeutic target. There is still a great deal to learn about how PEDF controls metabolic pathways in breast cancer and its metastatic form. Given this, the primary purpose of this study was to use a metabolomics approach to gain a better understanding of the mechanisms driving the reprogramming of metabolic events involved in breast cancer pertaining to PEDF under various glycaemic loads. We employed gas chromatography-quadrupole mass spectrometry (GC-Q-MS) to investigate metabolic changes in the triple-negative breast cancer (TNBC) cell line MDA-MB-231 treated with PEDF under glycaemic loading. Multivariate and univariate analyses were carried out as indicative tools via MetaboAnalyst (V.5.0) and R packages to identify the significantly altered metabolites in the MDA-MB-231 cell line after PEDF exposure under glycaemic loading. A total of 61 metabolites were found, of which nine were selected to be distinctively expressed in MDA-MB-231 cells under glycaemic conditions and exhibited differential responses to PEDF (p < 0.05, VIP > 1). Abnormalities in amino acid metabolism pathways were observed. In particular, glutamic acid, glutamine, and phenylalanine showed different levels of expression across different treatment groups. The lactate and glucose-6-phosphate production significantly increased in high-glucose vs. normal conditions while it decreased when the cells were exposed to PEDF, confirming the positive influence on the Warburg effect. The TCA cycle intermediates, including malate and citric acid, showed different patterns of expression. This is an important finding in understanding the link of PEDF with metabolic perturbation in TNBC cells in response to glycaemic conditions. Our findings suggest that PEDF significantly influenced the Warburg effect (as evidenced by the significantly lower levels of lactate), one of the well-known metabolic reprogramming pathways in cancer cells that may be responsive to metabolic-targeted therapeutic strategies. Moreover, our results demonstrated that GC-MS-based metabolomics is an effective tool for identifying metabolic changes in breast cancer cells after glycaemic stress or in response to PEDF treatment.